Strategi Penggunaan Media Audio Visual Untuk Meningkatkan Hasil Belajar Bahasa Inggris - Azura, Shafa Nabila (Universitas Muhammadiyah Muara Bungo, 2024)
In the world of education, students' English skills cannot be separated from the learning process provided by teachers. Lecturers, as instructors, strive to provide the best teaching and learning process for their students. English is a course that develops oral and written communication skills, understanding and expressing information. This course is no longer just a grammar course but can also develop students' English communication skills both orally and in writing. For this reason, a creative approach is needed to help students be more active and interesting in learning English. One of the methods proposed by the speakers is to learn English using audio-visual media, including videos, movies and music. In teaching English materials, using this learning material is one of the appropriate learning materials to use. The purpose of this review is to provide strategies for using audiovisual media to improve students' English learning outcomes. Technically, the strategy for using audiovisual media in the process of teaching and learning English is divided into 3 stages: preparation, use and the final stage is monitoring after use. This strategic use of media will make learning English more effective, interactive and enjoyable. Teachers will be more optimal in presenting material and students will understand the lesson more easily.